Pseudomonas aeruginosa or Pseudomonas pyocyanea? - HUGH, RUDOLPH; LESSEL, ERWIN F. (International Journal of Systematic and Evolutionary Microbiology, 1967)
ABSTRACT Recently the Judicial Commission of the International Committee on Nomenclature of Bacteria (ICNB) was asked to issue an Opinion conserving the name Pseudomonas pyocyanea (Gessard) Migula and rejecting the name Pseudomonas aeruginosa (Schroeter) Migula. In the present paper evidence is adduced that indicates Pseudomonas aeruginosa is not only the correct scientific name but also that which is in common usage internationally for the type species of the genus Pseudomonas Migula. In the interests of stable nomenclature and popular usage, the authors request that an Opinion be issued by the Judicial Commission, 1) placing the specific epithet aeruginosa, in the combination Pseudomonas aeruginosa (Schroeter) Migula, in the list of Epitheta specifica conservanda, and 2) placing the specific epithet pyocyanea, in the combination Pseudomonas pyocyanea Migula, in the list of Epitheta specifica reji-cienda.